Mini research projects as a mechanism to improve the quality of dementia care - Hava Golander (BMC, 2019)
Abstract Several models have been proposed to connect academia and practice in order to improve long-term care. In this paper we propose and describe the "Mini-Research Group" as an alternative model of such collaboration. The formation of mini-research groups was the unplanned by-product of a longitudinal action research project headed by the late Prof. Rebecca Bergman, a prominent nursing leader from the Department of Nursing at Tel-Aviv University. It involved a two-stage project aimed at developing, and later implementing, a specific tool to evaluate the quality of care provided in geropsychiatric units and to design a nursing intervention which entailed an improved model for care in specialized geropsychiatric units for persons with dementia. Initially, this article describes the projects that led to the development of mini-research groups, and then continues to describe several mini-research projects, focusing on the research questions which emerged from practice as well as the variety of methodologies used. Finally, we discuss the ways in which mini- research groups contributed to the quality of care for persons with dementia, benefited their families, professional staff, faculty participants, and advanced policy development. We argue that in light of the present array of ethical and legal restrictions which inhibit the recruitment of participants, using mini-research groups combined of practitioners and researchers, can provide a pragmatic solution, not only to overcome these barriers, but to improve the quality of care, stimulate clinical dementia research, and promote new insights into the lives of persons with dementia.